Spectroscopic insights into prodigiosin pigment production by Serratia marcescens - Ferraz, Ana Rita Simões (2024)
The appearance of cheese can be influenced by the intentional use of dyes such as paprika that color its rind, particularly in smear-ripened cheeses. In addition to this intentional addition, some microorganisms naturally present in cheeses can produce pigments that lead to color defects that negatively impact consumer acceptance and economic profitability. Serratia marcescens can produce a red pigment known as prodigiosin (Di Salvo, 2023). Prodigiosin is the most prominent secondary metabolite in the group of prodiginin compounds, with cycloprodigiosine, metacycloprodigiosine, undecylprodigiosin, prodigiosin R1, and streptorubin B (Stankovic et al., 2014). It was evaluated the prodigiosin production in two bacterial cultures Serratia marcescens ESACB 596 and Serratia marcescens ESACB 734, sourced from the Microbial Culture Collection of the Microbiology Laboratory of Polytechnic Institute of Castelo Branco, Portugal, with the aim to determine the optimal conditions to produce pink pigment. To achieve this, experiments were performed in three culture media (Luria Broth (LB), Nutritive Broth (NB) and Peptone Glycerol Phosphate (PGP), at two pH levels (7.5 and 8.0) and two different temperatures (22 °C and 28 °C).